Formation of political journalism as an institution in Azerbaijan: areas of development and activity - Guliyev, Bahruz (Cuestiones Políticas, 2020)
It analyses the methodological foundations and essence of political journalism as a social institution, as well as the interaction of politics and journalism. Based on an interdisciplinary study, the article gives an account of the peculiarities of the realization of political journalism in the world and in Azerbaijan, stating that political journalism performs informative, communicative, ideological, cultural, enlightening, organizational and recreational functions. It concludes by highlighting the power of the media to carry out democracy, in political decision-making and debates through the power of information. In other words, the power of the media is the power of political journalism, the unity of the media with political and economic power. It also points to the place and role of social media political science. Political media science is considered a new phenomenon in former Soviet republics. It is characterized as a phenomenon that encompasses systematic political theory, the science of modern comparative media, media, and politics. It is also believed that the political science of the media is related to the mediation of politics and the political processes of l to information.